2021
DOI: 10.3390/cleantechnol3010002
|View full text |Cite
|
Sign up to set email alerts
|

Economic and Sustainability of Biodiesel Production—A Systematic Literature Review

Abstract: As Earth’s fossil energy resources are limited, there is a growing need for renewable resources such as biodiesel. That is the reason why the social, economic and environmental impacts of biofuels became an important research topic in the last decade. Depleted stocks of crude oil and the significant level of environmental pollution encourage researchers and professionals to seek and find solutions. The study aims to analyze the economic and sustainability issues of biodiesel production by a systematic literatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(52 citation statements)
references
References 57 publications
0
27
0
1
Order By: Relevance
“…Renewable energy generally applies to the energy resources whose common characteristics are that they are non-exhaustible and naturally renewable. They are sources of clean inexhaustible energy and increasingly competitive ( Mizik and Gyarmat, 2021 ). Renewable energy resources are based on environmentally friendly technologies that convert biomass, solar, thermal or hydro powers to electricity and motor power.…”
Section: Sustaining Covid-19 Era Lockdown Environment Through Renewable Energy Resourcesmentioning
confidence: 99%
“…Renewable energy generally applies to the energy resources whose common characteristics are that they are non-exhaustible and naturally renewable. They are sources of clean inexhaustible energy and increasingly competitive ( Mizik and Gyarmat, 2021 ). Renewable energy resources are based on environmentally friendly technologies that convert biomass, solar, thermal or hydro powers to electricity and motor power.…”
Section: Sustaining Covid-19 Era Lockdown Environment Through Renewable Energy Resourcesmentioning
confidence: 99%
“…Schilling and Kelly [14] found that DOCH is more compatible with PVC in formulations with high contents of plasticizer (100 PHR or more) and, the blend of DOCH with other plasticizers showed a better performance in the range of 60-120 PHR. However, with the increasing restrictions of environmental policies and the imminent depletion of oil, more and more people are opting to replace fossil plasticizers with ones from renewable sources [15] .…”
Section: Introductionmentioning
confidence: 99%
“…Despite many strengths of microalgae technologies, the previous attempts to implement them in the EU have proven technological complexity, operational difficulties, and high investment expenditures of these operations [19,20]. The investment and operating costs required for microalgae cultivation are estimated to be a few to several times higher than those incurred for the production of lignocellulosic biomass [21,22].…”
Section: Introductionmentioning
confidence: 99%